Pengaruh Modifikasi Ovitrap Dengan Atraktan Rendaman Udang Terhadap Kepadatan Jentik Aedes sp - Sepdiyanto, Denik; Lusiana, Dina; Anwar, Andi (HIGIENE: Jurnal Kesehatan Lingkungan, 2020)
Dengue is a disease that causes outbreaks in Indonesia. Dengue is caused by Aedes sp. The higher density of mosquitoes in one place is the greater risk of developing dengue. The number of free larva in RT 18 Mangkurawang villages is only 8%, while the national standar is 95%, it indicates the density of mosquitoes in RT 18 very high. There is one way to control the Aedes sp. Which manage to reduce the density of the vector is the use of an egg trap (ovitrap) and to improve the effectiveness in reducing the number of mosquitoes, ovitrap is modified with shrimp marinade attractant. The aim of the research is to examine the effect of modifications ovitrap to the density of larva of Aedes sp to see the difference of Container Index (CI), House Index (HI), and Larva Free Index (LFI) at RT 18 Mangkurawang Village, Tenggarong. The research is a quasi eksperiment. The study was conducted in September until October 2017. The population was all houses in RT 18 and a sample of 15 houses for each treatment group. Analysis data in this study using a paired t-test and ANOVA test. Result showed the effect of modifications ovitrap of the density of Aedes sp (the reduction of CI, HI, and LFI) but has not reached the national standard density of mosquito larvae.The Health Department of Samarinda may recommended the modification ovitrap as a method of controlling the Aedes sp. Keywords: Aedes sp, attractant, shrimp marinade, ovitrap